APLIKASI SOAL HITUNGAN DASAR UNTUK ANAK BERBASIS ANDROID (Information Technology and Telematics, 2016)
Abstract– In the current era, many children - children who already have an android smartphone. Supposedly the android smartphone has a function that can be optimized as a medium of education of children, in addition to functioning as well as the media playing games, chatting, browsing and so on. Applications for the child about basic calculations based on android is intended as a medium of education of children in the form of matter, the question is a matter of basic calculations consisting of three (3) basic arithmetic operations, namely, addition, subtraction and multiplication. In this application the child - the child learns basic calculations work on the problems that have been provided and there is one tool that serves to directly assess the matter. This application is used on the Android operating system with at least version 2.2 Froyo (Frozen Yogurt) and will be compatible on mepunyai smartphone screen size 5.0 inch up to 5.5 inch. The application is made by using the Eclipse software, Android Emulator Genymotion, JAVA programming language, a dialect of XML for layout design applications Adobe Photoshop CS6 and CorelDraw X5 to design the logo, images, background and button. Keywords: smartphone, android, app, matter, basic calculations Abstrak –Pada era sekarang ini banyak anak - anak yang sudah mempunyai smartphone android. Seharusnya smartphone android tersebut mempunyai fungsi yang dapat dioptimalkan sebagai media edukasi anak, selain berfungsi juga sebagai media bermain game, chatting, browsing dan sebagainya. Aplikasi soal hitungan dasar untuk anak berbasis android ini bertujuan sebagai media edukasi anak yang berbentuk soal, soal tersebut merupakan soal hitungan dasar yang terdiri dari 3 (tiga) operasi hitung dasar yaitu, penjumlahan, pengurangan dan perkalian. Pada aplikasi ini anak – anak belajar mengerjakan soal hitungan dasar yang telah disediakan dan terdapat salah satu tools yang berfungsi untuk langsung menilai soal tersebut. Aplikasi ini digunakan pada sistem operasi Android dengan minimal versi 2.2 Froyo (Frozen Yogurt) dan akan compatible pada layar smartphone yang mepunyai ukuran 5.0 inch sampai dengan 5.5 inch. Aplikasi tersebut dibuat dengan menggunakan software Eclipse, Emulator Android Genymotion, bahasa pemrograman JAVA, bahasa XML untuk desain layout aplikasi Adobe Photoshop CS6 dan Coreldraw X5 untuk mendesain logo, gambar, background dan button.   Kata Kunci : smartphone, android, aplikasi, soal, hitungan dasar